2003
DOI: 10.1007/s00254-002-0716-7
|View full text |Cite
|
Sign up to set email alerts
|

Surface-water quality for the Salí River watershed in NW Argentina

Abstract: Spatial and temporal variations of Na, Mg, were monitored through 37 sampling stations to determine the main aspects influencing the surface-water quality in the Salí River watershed (Tucumán Province, NW Argentina). The influence of the regional geological setting on water chemistry allows to distinguish three subbasins. The interaction with sedimentary rocks was found to be dominant in the northern and centraleastern sub-basin as well as in the southern subbasin, whereas the metamorphic-granitic basement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…These values are similar to others observed in the region (Galindo et al, 1999) but much lower than those observed in other Pampean areas, such as La Pampa and Cordoba provinces (Nicolli et al, 1989;Smedley et al, 2002). One possible source of this trace element could be the volcanic ash in the sedimentary sequence, an interpretation also suggested in other regions of Argentina, such as Eastern Cordoba Province (Nicolli et al, 1989) and the Salí River watershed in NW Argentina (Fernandez-Turiel et al, 2003). At the northern part of La Pampa Province, Smedley and colleagues (2002) indicate primary magnetite and ilmenite as possible sources for As, as well as secondary Fe-Mn oxides in the loessoids.…”
Section: Water Qualitysupporting
confidence: 88%
“…These values are similar to others observed in the region (Galindo et al, 1999) but much lower than those observed in other Pampean areas, such as La Pampa and Cordoba provinces (Nicolli et al, 1989;Smedley et al, 2002). One possible source of this trace element could be the volcanic ash in the sedimentary sequence, an interpretation also suggested in other regions of Argentina, such as Eastern Cordoba Province (Nicolli et al, 1989) and the Salí River watershed in NW Argentina (Fernandez-Turiel et al, 2003). At the northern part of La Pampa Province, Smedley and colleagues (2002) indicate primary magnetite and ilmenite as possible sources for As, as well as secondary Fe-Mn oxides in the loessoids.…”
Section: Water Qualitysupporting
confidence: 88%
“…The effect of climate change was considered in 24 LTSEM systems, and international legislation was explicit in only 3 of these systems. Social–environmental studies were mainly focused on environmental quality (eg water and air conditions and urban solid wastes, n = 28), ecosystem services ( n = 25; eg Fernández-Turiel et al 2003), or the quantification of land-use and land-cover changes ( n = 24), and social aspects were usually disregarded (eg studies monitor environmental quality but do not explicitly quantify its effects on human health; Gramsch et al 2006). Only 4 of the identified LTSEMs focused solely on the social sciences (eg López-Sandoval and Maldonado 2019).…”
Section: Resultsmentioning
confidence: 99%
“…, 2003). Bottles were acid washed and rinsed three times with deionized water before bottles were re‐used to reduce container contamination and enhance sample preservation (Hall, 1998; Fernandez‐Turiel et al. , 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Two field duplicates were taken to increase precision and lab duplicates were used during analysis for quality control purposes (Carreón-Diazconti et al, 2003). Bottles were acid washed and rinsed three times with deionized water before bottles were re-used to reduce container contamination and enhance sample preservation (Hall, 1998;Fernandez-Turiel et al, 2003).…”
Section: Water Sample Collectionmentioning
confidence: 99%